2005
DOI: 10.1016/j.tet.2005.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tricyanovinyl-substituted thienylpyrroles and characterization of the solvatochromic, electrochemical and non-linear optical properties

Abstract: -Tricyanovinyl-substituted 1-(alkyl)aryl-2-(2´-thienyl)pyrroles 1 have been synthesized by direct tricyanovinylation reaction of 1-(alkyl)aryl-2-(2´-thienyl)pyrroles 2 using TCNE. The tricyanovinyl-derivatives 1 display dramatic reductions in both their optical and electrochemical band gaps relative to thienylpyrrole precursors 2. The solvatochromic behavior of compounds 1 was investigated in a variety of solvents. Hyper-Rayleigh scattering was used to measure the first hyperpolarizabilities β of the mentioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…[45] The arylthienyl moiety will act not only as a spacer but also as an auxiliary donor. These findings are in accordance with our recent work [19,[46][47][48] in which we concluded that the increase or decrease of the molecular nonlinear activity of heteroaromatic systems depends not only on the electronic nature of the (hetero)aromatic rings but also on the position of substitution of the donor or acceptor groups on these systems.…”
Section: Non-linear Optical Study Of Molybdenum Complexes 4-6supporting
confidence: 93%
“…[45] The arylthienyl moiety will act not only as a spacer but also as an auxiliary donor. These findings are in accordance with our recent work [19,[46][47][48] in which we concluded that the increase or decrease of the molecular nonlinear activity of heteroaromatic systems depends not only on the electronic nature of the (hetero)aromatic rings but also on the position of substitution of the donor or acceptor groups on these systems.…”
Section: Non-linear Optical Study Of Molybdenum Complexes 4-6supporting
confidence: 93%
“…spectra is observed when stronger acceptor groups are linked to the heterocyclic system. [8][9][10][11][12][19][20] As a result the substitution of a formyl group for a 2-(3-oxo-2,3-dihydroinden-1-ylidene)malononitrile moiety leads to a red shift of 170 nm from 348 nm (1a) to 510 nm (1e). Within the series 1a-e the CT bands moves to lower energy as the electron accepting ability of the acceptor moiety increases, in the order CHO < dicyanovinyl < rhodanine < thiobarbituric acid < 2-(3-oxo-2,3-dihydroinden-1-ylidene)malononitrile (Fig.…”
Section: Linear and Nonlinear Optical Properties Of The Chromophoresmentioning
confidence: 99%
“…Recently we were able to overcome these difficulties and reported on the interesting electrochemical and solvatochromic properties and the first hyperpolarizabilities of pyrrolecontaining NLO chromophores with potential application as nonlinear optical compounds. [8][9][10][11][12] We were therefore motivated to extend these studies and explore the potential of a novel series 1-(4-(thiophen-2-yl)phenyl)-1H-pyrroles 1 as efficient push-pull systems bearing pyrrole as donor group and dicyanovinyl, rhodanine, thiobarbituric acid and indanonedicyanovinyl as acceptor moieties linked through an arylthiophene spacer.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental [28], and theoretical [29][30][31] studies have demonstrated that replacing the benzene ring of a chromophore bridge with easily delocalizable five membered heteroaromatic rings as a pyrrole, results in an enhanced molecular polarizability of donor-acceptor compounds, where the pyrrole ring acts as electron-withdrawing structure [32]. Due to their solvatochromic, electrochemical and nonlinear optical properties, donor-acceptor pyrrole derivates could be employed for the manufacture of semiconductor materials or materials with strong NLO-responses [32,33]. Furthermore, pyrrole and oligomers synthesis has increased due to their application as electroluminescent devices [34].…”
Section: Synthesis and Modeling Of 25-disubstituted Pyrrole Compoundsmentioning
confidence: 99%